Lipid biosynthesis of Nitrosopumilus maritimus dissected by lipid specific radioisotope probing (lipid-RIP) under contrasting ammonium supply. (1st December 2018) - Evans, Thomas W.; Könneke, Martin; Lipp, Julius S.; Adhikari, Rishi R.; Taubner, Heidi; Elvert, Marcus; Hinrichs, Kai-Uwe
Abstract: Ammonia-oxidizing archaea (AOA) are among the most abundant microbes in the oceans and are one of the major sources of glycerol dibiphytanyl glycerol tetraethers (GDGTs) in the water column and underlying sediments. However, little is known about the mechanistic steps during biosynthesis of GDGTs that form the basis of the TEX86 paleothermometer. Recent results showed that, apart from temperature, physiological factors such as growth stage and variations of the ammonium oxidation rate may affect the TEX86 temperature proxy. We performed a short term incubation experiment with radiolabeled 14 C-bicarbonate to accurately trace the effect of high and low ammonium (NH4 + ) supply, on the production of individual membrane lipids by the AOA model organism Nitrosopumilus maritimus . The 14 C incorporation during growth was monitored at five time intervals by liquid chromatography coupled to flow-through scintillation counting of the hydrolyzed membrane lipid extract, allowing a straight forward and sensitive on-line detection of 14 C incorporation into archaeal lipids on time-scales lower than a single cell cycle. The experiments showed that low NH4 + supply results in higher cyclization of GDGTs with a preferential synthesis of crenarchaeol, whereas excess NH4 + led to predominant production of GDGT-0. Consequently, the cultures with a high NH4 + supply resulted in up to 10 °C lower estimated incubation temperatures than the cultures with low quantities of available NH4 + using the TEX86 L calibration. Interestingly, a high relative production of archaeol was observed at the beginning of all experiments (up to 27%), independent of the NH4 + supply; likewise the degree of cyclization was initially lowest indicating delayed production of cycloalkylated derivatives. This pattern is consistent with N. maritimus synthesizing GDGTs by head-to-head condensation of two archaeol molecules and subsequent cyclization of the resulting acyclic tetraether. This study provides robust information on the biosynthesis of GDGTs in N. maritimus and advances our understanding of the influence of NH4 + supply on the TEX86 proxy.